Optimization of the contents of Arabic gum, xanthan gum and orange oil affecting turbidity, average particle size, polydispersity index and density in orange beverage emulsion - Mirhosseini H.; Tan C.P.; Hamid N.S.A.; Yusof S. (2024)
Indexed by Scopus